2004
DOI: 10.1108/09540910410537354
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cycling reliability of lead‐free chip resistor solder joints

Abstract: The solder joint reliability of ceramic chip resistors assembled to laminate substrates has been a long time concern for systems exposed to harsh environments. In this work, the thermal cycling reliability of several 2512 chip resistor lead‐free solder joint configurations has been investigated. In an initial study, a comparison has been made between the solder joint reliabilities obtained with components fabricated with both tin‐lead and pure tin solder terminations. In the main portion of the reliability tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…This result implies that the reliability of SnAgCu alloys outperform SnPb for small components and vice versa for large components. This conclusion is consistent with the thermal fatigue experimental results that suggested that SnAgCu alloys outperform SnPb at low strain applications and vice versa at high-strain amplitude applications [14][15][16][17][18][19]. Figure 10.…”
Section: Effect Of Thermal Shocksupporting
confidence: 81%
“…This result implies that the reliability of SnAgCu alloys outperform SnPb for small components and vice versa for large components. This conclusion is consistent with the thermal fatigue experimental results that suggested that SnAgCu alloys outperform SnPb at low strain applications and vice versa at high-strain amplitude applications [14][15][16][17][18][19]. Figure 10.…”
Section: Effect Of Thermal Shocksupporting
confidence: 81%
“…23 It must be noted, however, that the size and distribution of the IMC particles in the initial microstructure of the Sn-8In-3Ag-0.5Cu joints in Ref. 23 did not correspond with the as-soldered microstructure of the SAC-In joints. This suggested that the Ag content has a major effect on the solidified microstructure and its recrystallization and subsequent coarsening during the TCT in In-containing lead-free solders, similarly to in hypoeutectic, eutectic, and hypereutectic ternary Sn-Ag-Cu alloys.…”
Section: Metallurgy Of Sac-in Jointsmentioning
confidence: 88%
“…Suhling et al 23 observed that Sn-8In-3Ag-0.5Cu joints (2512 resistor) revealed also a coarsening of the IMC particles during the TCT, although no quantitative analysis of the composition of the IMC particles and the Sn matrix was given. 23 It must be noted, however, that the size and distribution of the IMC particles in the initial microstructure of the Sn-8In-3Ag-0.5Cu joints in Ref. 23 did not correspond with the as-soldered microstructure of the SAC-In joints.…”
Section: Metallurgy Of Sac-in Jointsmentioning
confidence: 97%
See 1 more Smart Citation
“…9,[14][15][16] In addition to the solder strength and IMC thickness, some other factors such as the geometry of the joint, working temperature, microstructural evolution, roughness of the interface, and the amount of voids can affect the extent of the failure mode. 5,15,[17][18][19] The mechanics of the interfacial failure of solder joints were considered in several studies. 14,[20][21][22][23][24][25][26][27] Hayes et al 14 experimentally estimated the mode I fracture toughness of solder joints by performing high-strain-rate fracture tests on modified compact tension specimens.…”
Section: Introductionmentioning
confidence: 99%